TOLERANSI BERAGAMA MENURUT PERSPEKTIF ALWI SHIHAB - Taufik Mukmin (El-Ghiroh : Jurnal Studi Keislaman, 2017)
This research is titled Tela'ah Thought Alwi Shihab on Religious Tolerance in the Book of Inclusive Islam. This study aims to examine the various thoughts of Alwi Shihab in his book Islam Inclusive. To know how Alwi Shihab explains the various solutions and thoughts that he poured in his book Islam Inclusive. In today's reality we often find that the various conflicts between religious communities in various majorities and minorities of Muslims have become viral in the Netizen world about the persecution of the Rohingya Muslim community. examining the various thoughts of Alwi Shihab and by conducting literature study the authors found various thoughts of Islamic thought that supports the concept of religious tolerance in the offer Alwi shihab so that Alwi shihab thought this becomes something important contribution, especially in build attitude of religious tolerance. More to build tolerance in a group of religions who have different views to embody and revive the Islamic substance as Rahmatallil Alamin.